Epifitismo vascular e estado de conservação de fragmentos florestais na Bacia Hidrográfica do Sorocaba/Médio Tietê, São Paulo, Brasil - Bataghin, Fernando Antonio (2013)
About 10 % of all vascular plants in the world are epiphytes. Vascular epiphytes settle on the host trees (phorophytes) without producing haustorial structures, aiming to increase access to sunlight, even at the expense of humidity. The present study aimed to characterize the floristic, structure and spatial distribution of the vascular epiphytic community in protected and unprotected forest fragments located in the Sorocaba/Médio Tietê watershed (22º30 to 23º45 S, and 48º15 to 47º00 W). Given the size of the watershed it presents unique phytosociological conditions showing three vegetation types, allowing its division into downstream area, central area and upstream area, according to the characteristic vegetation of each area. The survey was conducted in 21 sampling sites (forest fragments), namely, seven in each area of the watershed. The vascular epiphyte component was quantitatively evaluated in 1090 phorophytes with DBH ≥ 20 cm and distributed in 12 sites (90 phorophytes each site and four sites in each area). The phorophytes were divided into six strata where the abundance of epiphytic species were recorded. In the total watershed 176 species, 66 genera and 14 families were recorded. The Shannon index for the watershed was H' = 3.695, the equability (J) = 0.713 and Margalef richness index (d) was 18.39. In the downstream area 56 species, 28 genera and nine families were found, with Shannon index H' = 2.948, equability J = 0.732 and Margalef richness d = 6.470. In this same area, 64% of species were anemochoric and 36% zoochoric, and the abundance of vascular epiphytes did not differ significantly (p > 0.05) among the Core Site (UC) and its replicas, however, there was significant difference (p < 0.05) between richness observed in the Core Site and its replicas, except the Replica II Site. In the downstream area, vertical distribution of vascular epiphytes varied significantly (p < 0.05) only between the Core Site and Replica I Site. For the Central Area 64 species, 32 genera and nine families were registered. H' = 2.872, J = 0.686 and d = 7.605. Regarding the dispersion syndrome, 56% of the species are anemochoric and 44%, zoochoric. There is a significant difference (p < 0.05) among the richness of the Core Site and Replica II and Replica III Sites, but no significant variation (p> 0.05) among the abundance of the Site Core and its replicas, nor between the vertical distribution of vascular epiphytes of the Core Site and its three replicas in the Central Area. In the upstream area 139 species, 61 genera and 14 families were found, with Shannon diversity index H'= 3.659, equability J = 0.742 and Margalef richness index d = 16.17. In this same area, 68% of the species showed anemochory and 32%, zoochory. The abundance of vascular epiphytes did not differ significantly (p > 0.05) among the Core Site and its Replica Sites, but the richness varied significantly (p < 0.01) among Core Site from all its replicas. There is a significant difference between the vertical distribution of vascular epiphytes occurring on the Core Site and its three replicas (p > 0.05) in the upstream area. Of the total of 176 species observed in the watershed, more than two thirds are anemochoric. The highest floristic similarity was observed between the downstream area and the central area, in turn, the upstream area had the highest number of exclusive species (94 spp.). No significant difference (p > 0.05) was observed between the distribution of abundance of vascular epiphytes on the different areas of watershed. The richness of the upstream 4 area was significantly different from the two other areas of the watershed, however, the central and downstream areas showed no significant difference between them. The vertical distribution of epiphytes were differently between the upstream and downstream areas, and between the central and upstream areas (p = 0.0001), but similar between the central and downstream areas (p > 0.05). The results emphasize the idea of dependence of the epiphytic community on atmospheric humidity. Among the main defining features of vascular epiphyte diversity of this study, the following should be highlighted: phytophysiognomic characteristics of the forest areas, macroclimatic factors (especially water seasonality) and factors influencing the microclimate of the fragments as the reduction of the structural complexity and the occurrence of forest edges. Regarding conservation, the presence of 50 species under some degree of threat should provide a strong argument for the conservation of forest fragments in the Sorocaba/Médio Tietê watershed.